Immediate effect of proprioceptive neuromuscular facilitation on scapular dyskinesia of volleyball players - Meneghini, Gisele Oltramari; Adamatti, Fernanda Silvestre; Dhein, William (Manual Therapy, Posturology & Rehabilitation Journal, 2020)
Background: Scapular dyskinesia can be caused by several factors, such as poor posture (thoracic kyphosis or cervical hyperlordosis) or changes in the activation and coordination of the scapular stabilizing muscles. Therefore, the term is correctly used when there is a change in the scapular biomechanics at rest or during movement. Objective: The objective of this study was to evaluate the effects of PNF on scapular dyskinesia of volleyball players. Methods: This is a quasi-experimental study with volleyball players. The study sample consisted of 32 individuals of both sexes, with ages between 14 and 17 years who presented scapular dyskinesia, identified by anamnesis and physical examination. To collect data, a sociodemographic evaluation developed by the researchers was used, containing personal data, pain evaluation through the Nordic Pain Questionnaire, and an image and video record was made for the analysis of photogrammetry and the Scapular Dyskinesia Test. For the data analysis a significance level of 5% was adopted. Results: Most of the sample (71.9%) practiced volleyball for more than a year, 65.6% trained three times a week, 84.4% were attackers, 96.9% were right-handed and 100% of the sample presented pain symptoms in the last twelve months. There was a significant difference in the abduction test of both scapulae and in the weight discharge of the right upper limb after the protocol. Conclusion: PNF has been shown to be effective in the initial phase of the treatment of scapular dyskinesia acting on neuromuscular balance and scapular orientation.